Suppressing Epidemic Spreading Via Differential Susceptibility Models - Afshar, Mehdi (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2018)
This paper considers the optimal control problem for some models using differential equations in epidemiology. In particular, we consider the differential susceptibility model(DS). Because of apparent diversity of examples, the idea of dividing susceptible population into two subgroups examined. For example in plenty of diseases, disease processes is different in male or female, children or adult, addicted or non-addicted, and so on. We show that it would be useful to consider this difference to reduce the costs in epidemic spreading. We want to exert some parameters in differential susceptibility model to control the epidemic spreading. The optimal control represents a drug treatment and Prevention strategies. Existence and uniqueness results for the optimal control are discussed. Finally, numerical examples are given for illustration.